2021
DOI: 10.1021/acs.langmuir.1c02119
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Ag–Cu Alloy Microflowers as SERS Substrates with Single-Molecule Detection Limit

Abstract: Bimetallic Ag–Cu alloy microflowers with tunable surface compositions were fabricated as surface-enhanced Raman spectroscopy (SERS) substrates with a limit of detection in the zeptomolar range for the analyte molecule rhodamine 6G (R6G). The substrates were prepared on a glass coverslip through a bottom-up strategy by simple thermolysis of metal-alkyl ammonium halide precursors. The reaction temperature and composition of the alloy were varied sequentially to find out the maximum SERS efficiency from the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…Surface-enhanced Raman scattering (SERS) is a convenient, nondestructive, and ultrasensitive molecular fingerprinting spectral method, and has been widely applied in chemical, biological, and food fields. In principle, SERS is mainly based on electromagnetic (EM) field enhancements localized in the gaps or junctions (hot spots) of nanostructures due to the interaction of incident laser light with the nanostructures. The enhancement factor depends on the size, shape, distribution, and material composition of the nanostructures. , The most widely used nanostructures are made of noble metallic nanomaterials, such as Ag or Au nanoparticles (NPs), Ag NPs@SiO 2 , Ag or Au nanowires, and bimetallic Ag–Cu alloy materials, , which exhibit high detection sensitivity. Especially, Ag nanostructures have been used to detect trace carbendazim residue recently ,, because the carbendazim tends to adsorb on the Ag surface due to interaction between the benzimidazole group of the carbendazim and Ag. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface-enhanced Raman scattering (SERS) is a convenient, nondestructive, and ultrasensitive molecular fingerprinting spectral method, and has been widely applied in chemical, biological, and food fields. In principle, SERS is mainly based on electromagnetic (EM) field enhancements localized in the gaps or junctions (hot spots) of nanostructures due to the interaction of incident laser light with the nanostructures. The enhancement factor depends on the size, shape, distribution, and material composition of the nanostructures. , The most widely used nanostructures are made of noble metallic nanomaterials, such as Ag or Au nanoparticles (NPs), Ag NPs@SiO 2 , Ag or Au nanowires, and bimetallic Ag–Cu alloy materials, , which exhibit high detection sensitivity. Especially, Ag nanostructures have been used to detect trace carbendazim residue recently ,, because the carbendazim tends to adsorb on the Ag surface due to interaction between the benzimidazole group of the carbendazim and Ag. , …”
Section: Introductionmentioning
confidence: 99%
“…The enhancement factor depends on the size, shape, distribution, and material composition of the nanostructures. 8,11−13 The most widely used nanostructures are made of noble metallic nanomaterials, such as Ag or Au nanoparticles (NPs), Ag NPs@SiO 2 , Ag or Au nanowires, 14−17 and bimetallic Ag−Cu alloy materials, 18,19 which exhibit high detection sensitivity. Especially, Ag nanostructures have been used to detect trace carbendazim residue recently 7,20,21 because the carbendazim tends to adsorb on the Ag surface due to interaction between the benzimidazole group of the carbendazim and Ag.…”
Section: Introductionmentioning
confidence: 99%
“…By measuring the SERS intensity of different microflower (MF) substrates, Sravani et al demonstrated that with an increasing amount of Cu in the Ag-Cu alloy, the intensity of a probe molecule R6G gradually increases compared with pure Ag MFs and can achieve the highest SERS intensity at 10% Cu. They achieved a 50-fold enhancement in SERS spectra with 10% Ag-Cu alloy microflowers, which supersedes the efficiency of pure Au-Ag MFs [ 180 ]. Bimetallic nanostructures with tunable morphology are of current interest in plasmonics, catalysis and SERS [ 175 ].…”
Section: Coppermentioning
confidence: 99%
“…17,18 Several sources in literature report the superior SERS activity of Ag-Au bimetallic nanoparticles, Ag-Cu nanostructures, and Ag-Au-Pt trimetallic nanostructures compared to the SERS activity of a single metal. [19][20][21] The substrates exhibit tunable plasmonic wavelengths by varying their composition, length and morphology. We have recently reported that the Ag capped Al nanorods (NRs) based an SERS substrate fabricated by the glancing angle deposition (GLAD) technique shows excellent SERS activity in the visible-NIR region.…”
Section: Introductionmentioning
confidence: 99%